A PGM-free Amperometric Sarcosine Biosensor Based on Iron-nitrogen-doped Carbon (Fe–N–C) Materials. Issue 7 (1st July 2022) - Xiao, Wenhuang; Zhao, Xiaolin; Lin, Luyin; Luo, Jian; Yang, Haipeng
Abstract : Sarcosine has been discovered as a better potential biomarker for Prostate cancer (PCa). Though many high-performance amperometric sarcosine biosensors have been reported, it is still difficult to accurately detect sarcosine because of the extremely low concentration and the presence of many electroactive interferents in human serum or urine. Since most of the reported sarcosine biosensors use platinum group metals (PGM) as catalysts, it is meaningful to explore other catalysts with higher catalytic activity. Metal-nitrogen-doped carbon (M–N–C) materials are considered as alternatives to precious metals. In this study, iron doped zeolitic-imidazolate-framework-8 (ZIF-8) composites were synthesized and calcined to obtain an Iron-nitrogen-doped Carbon (Fe–N–C) material, which has excellent catalytic activity. The sensitivity of the Fe–N–C modified sarcosine biosensor is 16.5 μ A mM −1, (234.2 μ A mM −1 cm −2 ), which is the highest one in recent reported works. It has a low limit of detection (LOD, 0.7 μ M, S/N = 3), and an appropriate linear detection range of 2–37 μ M. This work provides a new approach to prepare high performance sarcosine biosensors by improving the catalytic activity of the modifier of the sensor. It has great potential to be used as portable devices for the rapid detection of PCa.